Sustainable Livelihood Program in Selected Local Government Units of Rizal Province, Philippines: Basis for an Action Plan - Castillo, Joanna Ruth; Mantillas, Christopher (Journal of Interdisciplinary Perspectives, 2024)
This research assessed the Sustainable Livelihood Program's Micro-Enterprise Development Track, focusing on social preparation, resource mobilization, and participant mainstreaming while excluding pre-implementation, as beneficiaries still need to be involved at that stage. The researchers assessed beneficiaries' awareness and identified challenges faced by implementers. Data was gathered through cluster sampling from 150 out of 234 beneficiaries of Rodriguez, San Mateo, and Cainta in Rizal Province, Philippines, and nine implementers were purposefully selected. The findings indicated that the Seed Capital Fund was the primary assistance modality utilized by beneficiaries. However, beneficiaries had lower awareness of the two-day capability-building activities than other social preparation elements. Implementers encountered problems such as inadequate training evaluation tools, limited space, and the need for an SLP office. Although beneficiaries were generally aware that monitoring and assessment are crucial to government programs, challenges included insufficient contact information and unsustainable livelihood projects. An action plan was proposed to address these issues, focusing on enhancing the social preparation and program mainstreaming stages, using a mixed-method approach with a sequential explanatory design for data collection. By adopting this plan, program implementation may be enhanced. Additionally, the plan calls for follow-up studies to evaluate the livelihood program, assess its impact, and oversee the execution of the SLP Employment Facilitation Track, which remains part of the national government's SLP initiative.